Differences Between Indigenous Yeast Populations in Spontaneously Fermenting Musts From V. vinifera L. and V. labrusca L. Grapes Harvested in the Same Geographic Location - Raymond Eder, María L.; Conti, Francisco; Rosa, Alberto L. (Frontiers in Microbiology, 2018)
Yeast communities associated with Vitis vinifera L. ecosystems have been widely characterized. Less is known, however, about yeast communities present in grapes and fermenting musts from Vitis non-vinifera ecosystems. Moreover, there are no comparative studies concerning yeast communities in grapes from V. vinifera L. and non-vinifera Vitis species in vineyards from a shared terroir. In this work, we have used a culture-dependent strategy, phenotypic analyses, and molecular genotyping, to study the most representative yeast species present in spontaneously fermenting musts of grapes harvested from neighboring V. vinifera L. (cv. Malbec) and V. labrusca L. (cv. Isabella) vineyards. Phenotypic analyses of H2S production, ethanol tolerance and carbon utilization, on random selected strains of each Hanseniaspora uvarum, Starmerella bacillaris and Saccharomyces cerevisiae strains, as well as microsatellite genotyping of S. cerevisiae isolates from each the Malbec and Isabella grape musts, suggest that V. vinifera L. and V. labrusca L. ecosystems could harbor different yeast strain populations. Thus, microbial communities in exotic Vitis species may offer opportunities to look for unique yeast strains that could not be present in conventional V. vinifera L. ecosystems.